The Application Effect of Acupoint Sticking Combined with Spine-Pinching Therapy in the Stage of Remission of Asthma Disease in Children - Huang, Zhirong; Huang, Ting; Huang, Liling; Huang, Ruijie; Lu, Yan; Wang, Fengxing (Journal of Contemporary Medical Practice, 2025)
Objective: To explore the application effect of acupoint application combined with chiropractic therapy based on family intervention in children with asthma disease during the stage of remission. Methods: A total of 90 children with asthma disease in the stage of remission who visited the pediatric asthma outpatient clinic of our hospital from May 2022 to December 2023 were selected as the study subjects. They were randomly divided into a control group and an observation group, with 45 cases in each group, using a random number table method. The control group received conventional nursing care, while the observation group received acupoint application combined with chiropractic therapy based on family intervention. After 6 months of intervention, the changes in the number of upper respiratory tract infections, frequency of asthma disease attacks, syndrome/pattern of spleen deficiency scores, main symptom scores, asthma disease control status, recurrence rates, and Childhood Asthma Control Test (C-ACT) scores were compared between the two groups before and after the intervention. Results: The total control rate in the observation group was 93.33%, compared to 82.22% in the control group, with the observation group showing a significantly higher total control rate (P<0.05). The number of upper respiratory tract infections and asthma disease attacks in the observation group were fewer than those in the control group (P<0.05). The observation group also demonstrated superior improvements in syndrome of spleen deficiency symptom scores, primary symptom scores, and Childhood Asthma Control Test questionnaire scores compared to the control group (P<0.05). Conclusion: The acupoint application therapy combined with chiropractic spinal manipulation based on family intervention can effectively control asthma disease attacks, prevent upper respiratory tract infections, reduce the frequency of asthma disease episodes in children, regulate spleen function, and alleviate symptoms and signs. It is worthy of clinical promotion and application.